A PRELIMINARY STUDY OF POLISH STUDENTS’ APTITUDE FOR THINKING REFLEXIVELY, DIFFERENTIATED BY HIGHER EDUCATION FACULTIES AND THE LEVEL OF STUDY - Odrowąż-Coates, Anna; Perkowska-Klejman, Anna (Society Register, 2017)
The paper contains the original empirical study, based on quantified qualitative questionnaire, containing reflexivity scales - called QRT (Questionnaire to measure the Level of Reflexive Thinking) - developed by Kember et al. (2002) - translated, adjusted, validated and adopted to Polish circumstances. The aim was to compare the reflexivity levels amongst higher education students at differentiated faculties and at different levels of study (bachelor's, Master's and doctoral) to capture dependent variables and to promote reflexivity as a subject of scientific enquiry.